(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2025)
Waste management is an ongoing problem faced by various countries in the world, caused by our lack of awareness. Therefore, we need to prepare our next generation to have environmentally aware character and problem solving skills. This research aims to determine the effect of STEM learning on sustainable waste management topic towards students’ sustainable awareness. The method used in this research was quasi experimental with pretest-posttest non-equivalent control group design. Instrument used was questionnaire, which consist of 30 statements. The research sample was determined using the convenience sampling technique (n=134). Based on the findings, STEM learning on sustainable waste management topic can influence students’ sustainability awareness (p<,05).